Two Cannulated Screws Provide Sufficient Biomechanical Strength for Prophylactic Fixation in Adult Patients With an Aggressive Benign Femoral Neck Lesion - Fu, Guangtao; Zhong, Guoqing; Yang, Zehong; Cheng, Shi; Ma, Limin; Zhang, Yu (Frontiers in Bioengineering and Biotechnology, 2022)
Background Two cannulated screws were proposed for prophylactic fixation in adult patients with an aggressive benign femoral neck lesion in recent literature. However, the biomechanical properties of this intervention have not yet been investigated. Methods After the evaluation of heterogeneity of bone mineral density and geometry via quantitative computed tomography, twenty-four embalmed adult human cadaver femurs were randomized into the control, inferior half of the anterior cortical (25%) bone defect, entire anterior cortical (50%) bone defect, and 50% bone defect + two cannulated screws group. Biomechanical analysis was conducted to compare the stiffness and failure load among the four groups when mimicking a one-legged stance. A CT-based finite element analysis (FEA) was performed to mimic the cortical and cancellous bone defect as well as the implantation of two cannulated screws of the four groups. Measurements of the maximal displacement and von Mises stress were conducted with the longitudinal load force and boundary conditions being established for a one-leg-standing status. Results We noted a significant improvement of the failure load after the insertion of two 6.5mm cannulated screws in femurs with 50% bone defect (+95%, P=0.048), and no significant difference was found between the screw group and the intact femur. Similar trends were also found in the measurements of stiffness (+23%, P>0.05) via biomechanical testing, as well as the von Mises stresses (-71%, P=0.043) by FEA when comparing the screw group and the 50% bone defect group. Conclusion Our findings suggest that two cannulated screws provided sufficient biomechanical strength for prophylactic fixation in adult patients with an aggressive benign femoral neck lesion even the entire anterior cortical bone is involved.